VIRTUAL SCREENING OF STILBENE ANALOGUE AND INSILICO, IN VITRO ANTIPROTOZOAL EVALUATION OF LEAD MOLECULES - LALASA, G.; VIJAYARAJ, S.; THAMIZHVANAN, K.; CHAITHANYAVEENA, K. (International Journal of Current Pharmaceutical Research, 2017)
Objective: The objective of present study is the virtual screening of stilbene analogues followed by the in silico and in vitro evaluation for its anti protozoal activity. Methods: The method of virtual screening selected is the structure-based virtual screening using ChEMBL database. The in silico analysis was performed using auto dock tools 4.2. The docking was performed using 1T5F (Arginase I-OH complex) as the binding proteins which are drawn from the protein data bank. Results: The stilbene analogues from virtual screening are allowed to dock with the proteins the binding energies and docking positions were determined using auto dock tools 4.2. The in vitro evaluation of anti protozoal activity was performed. Conclusion: The stilbene analogues are capable of producing the antiprotozoal activity.